Diversified responses of vegetation carbon uptake to urbanization: a national-scale analysis - Zhang, Xueliang; Qiu, Dai; Xie, Yichun; Tu, Jianguang; Lan, Hai; Li, Xiaolei; Sha, Zongyao (Frontiers in Ecology and Evolution, 2023)
Urbanization converts vegetated lands into impervious surfaces and often degrades vegetation carbon sequestration in urban ecosystems. At the same time, the impact on urban vegetation growth from urban expansion could be spatially diverse given different natural environments and urban management practices. How to manage vegetation under rapid urbanization is an important topic for urban planning and management. We applied time-series remotely sensed images and analyzed the urban growth for all the prefecture-level cities across China during 2001-2019, and compared the impact of urbanization on vegetation carbon uptake proxied by MODIS (MOD17A2H) net primary productivity (NPP) on Google Earth Engine platform. At the national scale, the carbon uptake flux in urban areas was only 19% compared to that in the nonurban vegetated counterparts. The total urban area expanded by 22% and the vegetation carbon uptake in the newly urbanized zones was averagely reduced by 16% during the period with high heterogeneity and the exception of even improved NPP among cities, suggesting diversified responses from vegetation to urban sprawl. In addition, the changes of vegetation carbon sequestration in response to urbanization were spatially clustered, suggesting location-dependent factors affecting the urban vegetation health across the cities. Urban land management strategies unique to cities and regions may explain the diversified responses of vegetation carbon capture to urbanization and be cross-referenced when future urban planning and management optimization under different urban development contexts.